2021
DOI: 10.1002/dad2.12218
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal subfield imaging and fractional anisotropy show parallel changes in Alzheimer's disease tau progression using simultaneous tau‐PET/MRI at 3T

Abstract: Introduction: Alzheimer's disease (AD) is the most common form of dementia, characterized primarily by abnormal aggregation of two proteins, tau and amyloid beta. We assessed tau pathology and white matter connectivity changes in subfields of the hippocampus simultaneously in vivo in AD.Methods: Twenty-four subjects were scanned using simultaneous time-of-flight 18 F-PI-2620 tau positron emission tomography/3-Tesla magnetic resonance imaging and automated segmentation. Results:We observed extensive tau elevati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…However, FreeSurfer 6.0-based segmentation of hippocampal subfields from T 1 -weighted images with standard resolution (1 mm isotropic) has shown the ability to detect expected effects of AD (de Flores et al, 2015;Iglesias et al, 2015;Sämann et al, 2022). For diffusion MRI, expected biological effects were observed in previous studies on normal aging, AD pathology, and epilepsy using spatial resolution similar to the current study (Pereira et al, 2014;Wolf et al, 2015;Goubran et al, 2016;Carlson et al, 2021). Moreover, the top and bottom 5% data were excluded in calculating regional mean values to reduce partial volume effects.…”
Section: Discussionsupporting
confidence: 69%
“…However, FreeSurfer 6.0-based segmentation of hippocampal subfields from T 1 -weighted images with standard resolution (1 mm isotropic) has shown the ability to detect expected effects of AD (de Flores et al, 2015;Iglesias et al, 2015;Sämann et al, 2022). For diffusion MRI, expected biological effects were observed in previous studies on normal aging, AD pathology, and epilepsy using spatial resolution similar to the current study (Pereira et al, 2014;Wolf et al, 2015;Goubran et al, 2016;Carlson et al, 2021). Moreover, the top and bottom 5% data were excluded in calculating regional mean values to reduce partial volume effects.…”
Section: Discussionsupporting
confidence: 69%
“…Additionally, the NODDI model 28 was fitted to the same corrected data to obtain maps of orientation dispersion (ODI) and isotropic fraction (fiso). Although NODDI performs optimally with two nonzero b ‐values, it can deliver ODI and fiso maps with only one nonzero b ‐value 28,29 …”
Section: Methodsmentioning
confidence: 99%
“…Although NODDI performs optimally with two nonzero b-values, it can deliver ODI and fiso maps with only one nonzero b-value. 28,29 To quantify diffusion metrics among hippocampal subfields, we used the Automatic Segmentation of Hippocampal Subfields 30 tool on the T2-and T1-weighted images to segment the subfields of the hippocampus (DG, CA1, subiculum, entorhinal cortex, parahippocampal gyrus), using a previously developed atlas. 31 The subfields were then eroded by one voxel in the two-dimensional oblique coronal plane using c3d to reduce partial volume effects.…”
Section: Dti Processingmentioning
confidence: 99%
“…A DTI study in patients with FTD reported reduced FA values in the anterior corpus callosum, anterior and descending cingulum, and uncinate fiber tracts (Zhang et al, 2009;Torso et al, 2021). In comparison, in patients with AD, reduced FA was reported in the descending cingulum, posterior and anterior cingulum, and uncinate fiber tracts, correlating with the increased tau distribution assessed by PET (Kantarci et al, 2017;Jacobs et al, 2018;Sintini et al, 2019;Carlson et al, 2021). Thus, DTI may facilitate the differential diagnosis of FTD and AD in the clinical setting (Torso et al, 2021).…”
Section: Diffusion Imagingmentioning
confidence: 99%